Calcitonin induces collagen synthesis and osteoblastic differentiation in human periodontal ligament fibroblasts. (February 2017) - Wei, Yibo; Ye, Qing; Tang, Zhen; Tian, Gang; Zhu, Qiang; Gao, Haocheng; Wang, Dalin; Cao, Zhizhong
Highlights: CT is significantly higher expressed in the gingival crevicular fluid of patients with periodontitis. CT level is association with the occurrence and development of periodontitis. CT upregulates collagen expression through TGF-β1 mediated pathway in hPDLFs. CT induces osteoblastic differentiation of hPDLFs through BMP-2/4 mediated pathway in hPDLFs. Abstract: Background: Extracellular matrix (ECM) secretion and osteogenic differentiation in periodontal ligament fibroblasts (PDLF) facilitate the neogenesis of alveolar bone, which is the cellular basis for alveolar bone repair. Calcitonin (CT) has been reported to play an important role in promoting ECM expression and inducing osteogenic differentiation in osteoblast, but its effects on PDLFs remain obscure. Methods: The expression of CT, transforming growth factor-beta 1(TGF-β1) and bone morphogenetic protein (BMP) in gingival crevicular fluid (GCF) was measured by ELISA. The effects of CT on collagen synthesis and osteogenic differentiation in hPDLFs were investigated by using the primarily cultured hPDLFs infected with adenovirus carrying the CT gene. Gene expression was measured by quantitative PCR and western blot. Results: The expression of CT in gingival crevicular fluid (GCF) of patients with periodontitis was significantly higher than that of healthy subjects. In addition, CT expression correlated with the clinical indexes including probing pocket depth (PPD), clinical attachment level (CAL), and gingival index (GI). The in vitro study demonstrated that overexpression of CT by adenovirus infection increased the expression of TGF-β1, collagen type I and III, and osteoblastic markers including BMP-2/-4, alkaline phosphatase and osteocalcin in human PDLFs. Moreover, CT-enhanced collagen synthesis was abrogated in hPDLFs transfected with TGF-β1 siRNA, and CT-induced osteoblastic differentiation was blocked in hPDLFs by BMPs inhibitor noggin. Conclusions: These results suggest that CT promotes collagen synthesis and osteogenic differentiation in hPDLFs via the TGF-β1 and BMPs signaling pathways, respectively.